Small and Medium Firms, Aggregate Productivity and the Role of Dependencies - Paolo Fornaro; Henri Luomaranta (The Research Institute of the Finnish Economy (ETLA), 2017)
We analyze the productivity contribution of firms in the Finnish business sector, using data from 2002 until 2014, and assess the role of the dependency status (i.e. whether they are owned, at least partially, by a mother company) of small and medium enterprises in the manufacturing and services industries, together with the whole private business sector. We find that dependent firms have provided a larger contribution to aggregate productivity growth, compared to the independent ones, regardless of the industry, size class and age groups considered. This result is mainly driven by the better reallocation of labour among dependent companies and by the positive productivity contribution of dependent entrants. Inside the dependent category, the foreign controlled firms contribute more to the aggregate productivity than the other dependent companies due to even more efficient reallocation of labour inputs. Moreover, we find that dependent firms tend to reach their peak productivity earlier than their independent counterparts. Finally, we examine the subgroup of high growing enterprises and find that the positive effect of dependencies on the productivity contribution holds also for this class of firms.
Keywords: O12; O14; O47; 330; Productivity; Decomposition; Dependencies; Small and medium firms